RIFM fragrance ingredient safety assessment, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10-decahydro-5, 9-methanobenzocycloocten-11-one, CAS Registry Number 22690-27-3. (September 2018) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Francis, M.; Fryer, A.D.; et al.
Highlights: 1, 2, 3, 4, 5, 6, 7, 8, 9, 10-Decahydro-5, 9-methanobenzocycloocten-11-one, safety assessment based on RIFM's criteria. Safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.